Dielectric multilayers impact on radiation-induced charge accumulation in highly sensitive oxide field effect transistors - Bordoni, Camilla (2024)
Funding Information: The authors acknowledge the funding by the EU—NextGenerationEU—with funds made available by the National Recovery and Resilience Plan (NRRP) Mission 4, Component 1, Investment 4.1 (MD 351/2022)—NRRP Research. This work also received funding from the European Community’s Horizon Europe program (ERC-POC FLETRAD, Grant Agreement No. 101082283) and from National Funds through the FCT —Fundação para a Ciência e a Tecnologia, I.P.), Project Nos. LA/P/0037/2020, UIDP/50025/2020, and UIDB/50025/2020 of the Institute of Nanostructures, Nanomodelling and Nanofabrication—i3N. We would also like to acknowledge the Portuguese Foundation for Science and Technology, under the scope of doctoral Grant Nos. DFA/BD/8335/2020 and 2022.09516.BD, for the support. Publisher Copyright: © 2024 Author(s).